Enhancing Maritime Safety Awareness Through Simulation-Based Training for Fishermen in Raam Island - Gumelar, Fajar; Sumarta, Ryan Puby; Muhammad, Fadel; Filemon, Filemon; Ikbal, Iqdam Mukaddim (Community Development Journal, 2025)
Maritime accidents in small-scale coastal communities are often caused by low awareness and limited knowledge of safety practices among traditional fishermen. Pulau Raam, located in Southwest Papua, is one such community where most fishermen have never received formal maritime safety training. This community service program aimed to improve fishermen’s safety knowledge and preparedness through a structured educational intervention. The method applied combined theoretical instruction, practical simulation, and provision of safety equipment. The participants consisted of 30 traditional fishermen who rely on small long boats for daily activities. The intervention began with introductory sessions that introduced the importance of life-saving equipment and safe behavior at sea. This was followed by hands-on simulations involving the correct use of life jackets, identification of dangerous weather, and basic emergency response. To assess the effectiveness of the program, a pre-test and post-test were administered to all participants. The results showed a statistically significant improvement in knowledge, with post-test scores increasing from a mean of 48.5 to 83.7 (p < 0.05). Additionally, the provision of life jackets supported the immediate application of learned safety practices. This program demonstrates that combining localized education, practical skill-building, and equipment access can substantially enhance safety awareness and behavior among fishermen. It offers a replicable model for other coastal communities in Indonesia with similar challenges. Further efforts should include community mentoring and institutional collaboration to sustain safety practices in the long term.